THE SAFETY OF CIVIL AVIATION AS A COMPLEX CONCEPT - Філіппов, А. В. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2007)
The article examines the complex concept of "civil aviation security" and its components. Based on the scientific analysis of the current legislation of Ukraine, international law and scientific literature offered the author’s definition of these concepts.